COMPREHENSIVE STUDY OF THE EFFECT OF VOLUME PULSE LASER HARDENING (VPLH) ON THE RESISTANCE OF HARD ALLOYS CUTTING TOOLS - Igor Aleksandrovich Pinahin; Stanislav Aleksandrovich Toeskin (Вестник Северо-Кавказского федерального университета, 2022)
Results of influence studies of raising toughness of instruments are considered in the article from hard alloys by the method of pulsed lazer processing.